2006
DOI: 10.1037/0096-1523.32.5.1276
|View full text |Cite
|
Sign up to set email alerts
|

Does a regional accent perturb speech processing?

Abstract: The processing costs involved in regional accent normalization were evaluated by measuring differences in lexical decision latencies for targets placed at the end of sentences with different French regional accents. Over a series of 6 experiments, the authors examined the time course of comprehension disruption by manipulating the duration and presentation conditions of accented speech. Taken together, the findings of these experiments indicate that regional accent normalization involves a short-term adjustmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
221
8
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 177 publications
(251 citation statements)
references
References 46 publications
18
221
8
4
Order By: Relevance
“…This shows that dialect differences not only influence the perception of the first language (Floccia et al, 2006;Sumner & Samuel, 2009), but also affect the learning of a second language.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This shows that dialect differences not only influence the perception of the first language (Floccia et al, 2006;Sumner & Samuel, 2009), but also affect the learning of a second language.…”
Section: Discussionmentioning
confidence: 99%
“…These two varieties both lack the English /e/-/ae/ contrast, but differ in the phonetic realization of the Dutch front vowel /e/ (see Section 1.1). Previous studies have shown that dialect differences can have strong effects on the perception of the native language (Floccia, Goslin, Girard, & Konopczynski, 2006;Sumner & Samuel, 2009). This suggests that it is worthwhile to investigate how dialect differences influence the perception of a second language.…”
Section: Introductionmentioning
confidence: 99%
“…Floccia, Butler, Goslin, and Ellis (2009), for example, have argued that foreign accents tend to affect all phonemes, whereas dialects mainly affect vowels. With respect to perceived accentedness, regional accents are also judged to be more similar to the standard variety of a language than foreign accents are (Floccia, Goslin, Girard, & Konopcynski, 2006). But although foreign-accented speech may deviate more strongly from the standard pronunciation than native accents do, the task of the listener stays the same, namely to recognize intended words despite their variability.…”
Section: Introductionmentioning
confidence: 92%
“…There are relatively few studies looking at the cost of regional accents in word recognition. The few studies that have investigated processing costs caused by within-language accents have found that unfamiliar regional accents initially slow down the identification of target words in continuous speech (Floccia et al, 2009;Floccia et al, 2006). Evans and Iverson (2004) first showed that adaptation to regional accents depends on the native dialect of the listeners.…”
Section: Experiments 2: Auditory Lexical Decision Taskmentioning
confidence: 99%
“…A great deal of recent research has shown that it is necessary to consider the differences and commonalities between bilinguals' and monolinguals' speech processing. Our study thus tests whether bilinguals' linguistic experience affects the way they adjust to regional accents, as it does in monolinguals (e.g., Conrey et al, 2005;Dufour et al, 2013;Floccia, Butler, Goslin, & Ellis, 2009;Floccia et al, 2006).…”
Section: Introductionmentioning
confidence: 99%